Quality of life in children with CF: Psychometrics and relations with stress and mealtime behaviors. Issue 6 (30th December 2014) - Driscoll, Kimberly A.; Modi, Avani C.; Filigno, Stephanie S.; Brannon, Erin E.; Chamberlin, Leigh Ann; Stark, Lori J.; Powers, Scott W.
Summary Background The purpose of this study was to evaluate the utility of the Cystic Fibrosis Questionnaire‐Revised (CFQ‐R) with toddlers and preschool‐aged children. Clinically relevant relations between health‐related quality of life (HRQOL), stress, and mealtime behaviors have not been examined. It was hypothesized that problematic mealtime behaviors and increased stress would be negatively associated with HRQOL. Methods Parents of 73 children (2–6 years) with CF completed questionnaires assessing their children's generic (PedsQL) and CF‐specific HRQOL, parenting and CF‐specific stress, and mealtime behaviors. Results CFQ‐R Physical, Eating, and Respiratory HRQOL subscales had acceptable to strong reliability (alphas = 0.73–0.86); other scales approached acceptable reliability. Lower CF‐specific stress was associated with higher CFQ‐R Eating HRQOL (B = −0.84; P < 0.05) scores. Fewer eating problems were associated with higher CFQ‐R Eating (B = −1.17; P < 0.0001) and Weight HRQOL (B = −0.78; P < 0.01) scores. Conclusions As hypothesized, problematic eating and higher CF‐specific stress was associated with lower CF‐specific HRQOL. The CFQ‐R has promise for use in young children with CF, but will need to be modified to exchange items not relevant to preschoolers with items that are more relevant to this age group. Pediatr Pulmonol. 2015; 50:560–567. © 2014 Wiley Periodicals, Inc.